Seasonal Analysis of Dissolved Organic Carbon in a Tropical Wetland Using UAV Technology - Guzman López, Wilfer David; Giraldo Buitrago, Lina Claudia; Vélez Macías, Fabio de Jesús; Aguirre Ramírez, Néstor Jaime (Revista Científica, 2025)
Dissolved organic carbon (DOC) plays a key role in the global carbon cycle and the biogeochemical dynamics of aquatic ecosystems. In this study, an empirical model was applied to imagery from unmanned aerial vehicles, which were acquired during two hydrological periods (low water in February and high water in December), in order to assess the seasonal dynamics of DOC in El Eneal wetland. The Kruskal-Wallis test revealed significant differences (p=0.00015) in the DOC concentrations between periods, confirming the regulatory effect of the water level. Shifts in spectral signatures indicated variations in the molecular composition of DOC, with an increased blue reflectance observed during the high-water period. Reductions of up to 18% in vegetated zones were attributed to dilution, retention, and mineralization processes, whereas unvegetated areas exhibited only a 2% decrease. These findings underscore the influence of the hydrological cycle on DOC dynamics in tropical wetlands.